Evidence-based public health - Brownson, Ross C. (New York ; Oxford : Oxford University Press, 2003)
Public health decisions are often based on short-term demands rather than long-term study, and policies & programs are sometimes developed from anecdotal evidence. To enhance evidence-based practice, this book provides practical guidance on the methodology and evaluation of such programs & policies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Public health; Evidence-based medicine